A review of the clinical utility of the Enhanced Liver Fibrosis test in multiple aetiologies of chronic liver disease. (January 2020) - Patel, Preya Janubhai; Connoley, Declan; Rhodes, Freya; Srivastava, Ankur; Rosenberg, William
The rising incidence of chronic liver disease continues to be an increasing health burden. The morbidity and mortality associated with chronic liver disease typically occur in patients with advanced fibrosis. Hence, early identification of those at-risk is of vital importance to ensure appropriate ongoing management. Currently, tools for appropriate risk stratification remain limited. Increasing awareness of the limitations of liver biopsy has driven research into alternative non-invasive methods of fibrosis assessment including serological markers assessing functional changes. One such biomarker, the Enhanced Liver Fibrosis test, was initially validated in a cohort of 1021 patients with mixed aetiology chronic liver disease and shown to perform well. Since this pathfinder study, it has been independently validated in cohorts of hepatitis C, non-alcoholic fatty liver disease, alcoholic liver disease, primary biliary cirrhosis and primary sclerosing cholangitis. In addition to performing well as a diagnostic tool, the Enhanced Liver Fibrosis test has been shown to outperform liver biopsy in prognostic studies and is the only non-invasive marker to do so. However, questions remain regarding the use of this test, particularly regarding the possible effect age and alcohol may have on test scores. This review examines the current literature published in relation to the Enhanced Liver Fibrosis test and its clinical utility and highlights areas requiring further study.